The relationship between parenting styles of parents and emotional intelligence and aggression among teenage girls - Khosravi , Maryam; Sadeghi , Jamal (Applied Family Therapy Journal (AFTJ), 2020)
Aim: This research aimed to determine the relationship between parenting styles and emotional intelligence and aggression among teenage girls. Method: The study was correlational and its statistical population included 1149 high school girl students in Amol city in the first semester of the academic year 2018-2019. In this population, 234 people were randomly selected and completed the questionnaires of Baumrind Parenting Styles (1973), Schutte Emotional Intelligence, and Buss–Perry Aggression Questionnaire (1992). The data were analyzed by Pearson analysis and multivariate regression using SPSS 21 software. Results: The findings indicated a relationship between the parenting style of parents and emotional intelligence and aggression among girls (P = 0.01). There is also a relationship between parenting styles and emotional intelligence. Also, there is a relationship between parenting style and aggression among girls (P = 0.01). Conclusion: The parenting style of parents can play both supportive and non-supportive roles, the use of which can impact the child’s development and growth in the field of emotional intelligence and the emergence of aggression.